Australian women's perceptions and practice of sleep position in late pregnancy: An online survey. Issue 2 (March 2022) - Warrilow, K.A.; Gordon, A.; Andrews, C.J.; Boyle, F.M.; Wojcieszek, A.M.; Stuart Butler, D.; Ellwood, D.; Middleton, P.F.; Cronin, R.; Flenady, V.J.
Abstract: Background: Going-to-sleep in the supine position in later pregnancy (≥28 weeks) has been identified as a risk factor for stillbirth. Internationally, public awareness campaigns have been undertaken encouraging women to sleep on their side during late pregnancy. Aim: This study aimed to identify sleep practices, attitudes and knowledge in pregnant women, to inform an Australian safe sleeping campaign. Methods: A web-based survey of pregnant women ≥28 weeks' gestation conducted from November 2017 to January 2018. The survey was adapted from international sleep surveys and disseminated via pregnancy websites and social media platforms. Findings: Three hundred and fifty-two women participated. Five (1.6%) reported going to sleep in the supine position. Most (87.8%) had received information on the importance of side-sleeping in pregnancy. Information was received from a variety of sources including maternity care providers (186; 66.2%) and the internet (177; 63.0%). Women were more likely to report going to sleep on their side if they had received advice to do so (OR 2.3; 95% CI 1.0–5.1). Thirteen (10.8%) reported receiving unsafe advice, including changing their going-to-sleep position to the supine position. Discussion: This indicates high level awareness and practice of safe late-pregnancy going-to-sleep position in participants. Opportunities remain for improvement in the information provided, and understanding needs of specific groups including Aboriginal and Torres Strait Islander women. Conclusion: Findings suggest Australian women understand the importance of sleeping position in late pregnancy. Inconsistencies in information provided remain and may be addressed through public awareness campaigns targeting women and their care providers.